Słowo w ewolucji. Kłamstwa, seks, plotki i… znajomi na Facebooku - Wężowicz-Ziółkowska, Dobrosława (Wydawnictwo Naukowe UAM, 2013)
The essay shows the main conceptions upon a biological power of a word: the macchiavellian theory/ theory of a lie, the mating mind theory, that means a theory of handicaps, and the social selection theory of S. Dunbar. The author proposes a thesis that a speech takes its power from the biological determinants of the origin of a language, and proves it by fusing various contemporary biological concepts. It is a biological evolution that founds the power of words, and also explains the magic of words in the various types of relations – among society, but also between sexes, generations and finally, among individuals considered in a biological sense.
Word in Evolution. Lies, Sex, Gossips and... Friends on Facebook
Keywords: word; evolution; adaptation; sex; deceit; gossip; natural selection; sexual selection